Utopianism and social change: Materialism, conflict and pluralism. (October 2018) - Martell, Luke
This article discusses criticisms that utopia and utopianism undermine social change. It outlines two types of utopia, future and current. It argues against claims that utopianism is idealist and steps aside from material and conflictual dimensions of society and so undermines change, proposing that utopias are material and conflictual and contribute to change. Against liberal and pluralist criticisms that utopianism is end-ist and totalitarian and terminates diversity and change, it argues that utopianism can encompass liberal and pluralist dimensions and be dynamic rather than static. It is proposed that criticisms create false conflations and dichotomies. Critical perspectives, rather than being rejected, are answered on their own terms. Utopianism, it is argued, is part of change, materially, now and in the future.